PENGARUH COMPUTER BASED INSTRUCTION MODEL SIMULASI BERBASIS MULTIMEDIA INTERAKTIF TERHADAP RASA INGIN TAHU SISWA PADA PEMBELAJARAN IPA - Kun Hisnan Hajron (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2021)
The aim of this study is to explain the influences of computer based instruction, interactive multimedia-based simulation model on the curiosity of the fourth grade students. The design of this study uses a quasi experiment method with nonequivalent control-group design. The classes used were class IVA, IVB, and IVC with with each student numbers 24, 29, and 26. In this study, class IVA is used as a control class, while class IVB and class IVC as an experimental class. The results of the pretest showed that the curiosity of IVA students (control) was 65, while the post-test was 76.66. In class IVB (experiment 1) shows that, at pretest it was 63.44 and post-test 81. Meanwhile in the IVC (experiment 2) class the pretest was 61.53 and post-test 82.3. Thus the results of the Independent Sample T-test for students' curiosity showed significance (p) 0.041 <0.05 so Ho was rejected. This shows that, there are significant differences in curiosity of students who use computer based instruction products, interactive multimedia-based simulation models (experimental class) with those using conventional models (control class). With these results, it is expected to add to the repertoire of knowledge and alternative ways for teachers to influence students' curiosity, so that the development potential of students in the learning process becomes maximal.